The Approach of Ma’had al-Jami’ah in Character Building for Students at UIN Sunan Ampel Surabaya - Rifa'i, Bahtiyar; Shofi, Ibnus; Alfisuma, Meria Zakiyah (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2025)
Education holds significant potential in improving morality through holistic character education. Character education is not merely about enhancing students' intellect but also about shaping their personality and fostering noble character. This form of education goes beyond imparting moral knowledge in the classroom; it also includes practical guidance for daily life. This study aims to examine the models of approach employed by Ma'had al-Jami'ah in shaping students' character, the outcomes of these models, and the challenges faced by the Ma'had.The research method used is qualitative with a descriptive-analytical approach. In this approach, the researcher describes the findings in the field while analyzing how the data supports the hypothesis in relation to the issues raised. The findings of the study indicate: (1) The models employed by the Ma'had in developing the good character of the students include fostering positive habits, providing exemplary role models, instilling discipline, and offering participatory learning. (2) The resulting character traits are a commitment to worship and study, discipline, and respect for differences. (3) Several challenges were identified, including the lack of optimal awareness among students, inadequate facilities and infrastructure at Ma'had al-Jami'ah, and the diverse backgrounds of the students. However, over time, these challenges have been addressed through adaptation.